Perception of Non-Malay Malaysians Towards the Jawi Script as a National Heritage - Ramli, Ahmad Fahmi (Issues in Language Studies, 2021)
The Jawi script is a Malay traditional writing system adapted from the Arabic alphabet which was once used widely during the reign of the British Empire before Romanisation of the Malay writing system took place. It is regarded as a national heritage of Malaysia due to the fact that Bahasa Melayu is the national language of the country. There have been many initiatives taken by the government in preserving the Jawi script including the insertion of Jawi lessons in the Bahasa Melayu subject at the primary school level. However, the new education policy has roused an argument among Malaysians, particularly non-Malays who have been in disagreement towards the new syllabus implemented. The study examined the perceptions and attitudes of non-Malays in Malaysia towards the Jawi script. This descriptive study involved 30 respondents who were approached and invited to participate in the survey. The result portrayed that the participants showed neutral perceptions towards the Jawi script on the basis that it has its own artistic values that should be preserved.